2021
DOI: 10.1080/10717544.2021.1949075
|View full text |Cite
|
Sign up to set email alerts
|

Aging erythrocyte membranes as biomimetic nanometer carriers of liver-targeting chromium poisoning treatment

Abstract: Chromium poisoning has become one of the most common heavy metal poisoning occupational diseases with high morbidity and mortality. However, most antidotes detoxify the whole body and are highly toxic. To achieve hepato-targeted chromium poisoning detoxification, a novel hepato-targeted strategy was developed using aging erythrocyte membranes (AEMs) as biomimetic material coated with a dimercaptosuccinic acid (DMSA) nanostructured lipid carrier to construct a biomimetic nanodrug delivery system. The particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…NPs adsorbed to RBCs could avoid MPS uptake, which prolonged their circulation time. A macrophage uptake experiment was used to evaluate the anti-phagocytosis abilities of RBC-PNPs and RBC-CSPNPs ( Yao et al, 2021 ). The fluorescence intensity of Cy5.5-PNPs and Cy5.5-CSPNPs groups were significantly higher than those of the RBC-Cy5.5-PNPs and RBC-Cy5.5-CSPNPs groups, implying rapid clearance of PNPs and CSPNPs in vivo ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NPs adsorbed to RBCs could avoid MPS uptake, which prolonged their circulation time. A macrophage uptake experiment was used to evaluate the anti-phagocytosis abilities of RBC-PNPs and RBC-CSPNPs ( Yao et al, 2021 ). The fluorescence intensity of Cy5.5-PNPs and Cy5.5-CSPNPs groups were significantly higher than those of the RBC-Cy5.5-PNPs and RBC-Cy5.5-CSPNPs groups, implying rapid clearance of PNPs and CSPNPs in vivo ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To verify whether MM-NLCs inherit the immunological characteristics of macrophages, the in vitro antiphagocytosis assay was first conducted. RAW264.7 cells were utilized as a cell model to reckon the stealth power of the biomimetic nanosystem (Xuan et al., 2016 ; Yao et al., 2021 ). The captured images showed that a less fluorescence level in macrophages treated with MM-NLCs than in the bare NLCs group ( Figure 4(A) ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we also examined the microviscosity of the interior of the erythrocyte in the presence and absence of C 60 (OH) 36 . Aging of erythrocytes is accompanied by an increase in the cell microviscosity of cells [46] because of a decrease in intracellular electrolyte concentration, a lower water content, and a reduction in cell diameter, volume, and surface area [32,47]. The cytoplasmic microviscosity of the interior of erythrocytes is determined mainly by the concentration of hemoglobin, but also depends on the water content of the cell [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mature human erythrocytes constitute a convenient research model to study oxidative damage during prolonged incubation, which triggers ROS-mediated damage [ 30 , 31 , 32 , 33 , 34 ]. The source of ROS in erythrocytes is hemoglobin, which undergoes autoxidation to methemoglobin producing O 2 •− [ 30 ].…”
Section: Introductionmentioning
confidence: 99%